2009
DOI: 10.1177/1358863x09106619
|View full text |Cite
|
Sign up to set email alerts
|

Increased intima thickness of the radial artery in patients with coronary heart disease

Abstract: Ultrabiomicroscopy is a novel high-frequency (55 MHz) ultrasound technique that could be used to non-invasively measure the vessel wall and separate the intima-media complex into measurements of intima and media thickness. Since no previous study has measured intima and media thickness separately in vivo in patients with coronary heart disease (CHD), the aim of the current study was to measure intima and intima-media thickness of the radial and the anterior tibial arteries among patients with CHD and healthy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Notably, we identified a trend manifested as obvious intimal hyperplasia combined with mature plaque involving the RA in patients presenting with overt coronary disease. However, no differences in the media layer were demonstrated among our three groups, a similar observation to that made using ultrabiomicroscopy in a comparison between patients with and without CAD [ 4 ]. Xu and associates reported that RA intimal thickness measured by ultrasound biomicroscopy could detect CAD independently similarly to that of carotid intima-media thickness [ 3 ].…”
Section: Discussionsupporting
confidence: 87%
“…Notably, we identified a trend manifested as obvious intimal hyperplasia combined with mature plaque involving the RA in patients presenting with overt coronary disease. However, no differences in the media layer were demonstrated among our three groups, a similar observation to that made using ultrabiomicroscopy in a comparison between patients with and without CAD [ 4 ]. Xu and associates reported that RA intimal thickness measured by ultrasound biomicroscopy could detect CAD independently similarly to that of carotid intima-media thickness [ 3 ].…”
Section: Discussionsupporting
confidence: 87%
“…A recent study of radial arteries in apparently health individuals observed that the intimal thickness was <10 μm in 90% of those studied 14 . The median vascular intimal thickness in our CKD patients was 12.5 (IQR, 6.1-26.5) μm for the arteries and 6.4 (IQR, 4.4-12.2) μm for the veins (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
“…21 In this highly hydrated state, the collagen gel was too fragile to be handled. Puncturing the gel with the curved needle from a 10-0 suture invariably tore apart the entire gel.…”
Section: Native Collagen Gels Did Not Withstand Suturingmentioning
confidence: 99%